On a new variant of F-contractive mappings with application to fractional differential equations - Patle, Pradip Ramesh; Gabeleh, Moosa (Nonlinear Analysis: Modelling and Control, 2022)
The present article intends to prove the existence of best proximity points (pairs) using the notion of measure of noncompactness. We introduce generalized classes of cyclic (noncyclic) F-contractive operators, and then derive best proximity point (pair) results in Banach (strictly convex Banach) spaces. This work includes some of the recent results as corollaries. We apply these conclusions to prove the existence of optimum solutions for a system of Hilfer fractionaldifferential equations.
Keywords: best proximity point; measure of noncompactness; F-contractive operator; fractional differential equation